Pengaruh Mekanisme Good Corporate Governance terhadap Potensi Manipulasi Laporan Keuangan yang diukur dengan Beneish M-Score pada Perusahaan Sektor Healthcare di Bursa Efek Indonesia Periode 2023-2024 - Qurrotul Aini; Zahra Nazila Faiza; Farichatur Rizkiyah; Rafael Dian Omega; Felisha Berliana Putri; Rohmawati Kusumaningtias; Ambar Kusumaningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the effect of Good Corporate Governance mechanisms on the potential for financial statement manipulation in healthcare companies listed on the Indonesia Stock Exchange during the 2023–2024 period. Financial statement manipulation remains a serious issue because it reduces the reliability of financial reporting and may mislead investors and other stakeholders. This research focuses on three governance mechanisms, namely audit committee, managerial ownership, and institutional ownership, while the potential manipulation of financial statements is measured using the Beneish M-Score model. The study applies a quantitative approach with an associative research design. The sample was selected using purposive sampling and consists of 22 healthcare companies, resulting in 44 observations. Data analysis was conducted through descriptive statistics, classical assumption tests, and multiple linear regression analysis. The findings indicate that managerial ownership has a significant negative effect on the potential for financial statement manipulation, suggesting that higher managerial share ownership can reduce opportunistic behavior by management. Institutional ownership does not show a significant influence on financial statement manipulation. Meanwhile, the audit committee variable could not be analyzed further because it lacked sufficient data variation among the observed companies.